login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

Solution of the equation a(n) = a(n-2) + b(n-2), where a( ) and b( ) are increasing sequences of positive integers such that every positive integer is in one of them and only one term is in both.
16

%I #8 Dec 02 2017 21:00:42

%S 1,2,4,6,9,13,17,23,28,35,42,50,58,68,77,88,98,110,122,135,148,162,

%T 177,192,208,224,241,258,277,295,315,334,355,375,398,419,443,465,490,

%U 513,539,564,591,617,645,672,701,729,760,789,821,851,884,915,949,981

%N Solution of the equation a(n) = a(n-2) + b(n-2), where a( ) and b( ) are increasing sequences of positive integers such that every positive integer is in one of them and only one term is in both.

%C The increasing complementary sequences a() and b() are uniquely determined by the titular equation and initial values. The initial values sequences in the following guide are a(0) = 1, a(1) = 2, b(0) = 3.

%C A294860: a(n) = a(n-2) + b(n-2); not quite complementary

%C A022939: a(n) = a(n-2) + b(n-2); offset 1, complementary

%C A294861: a(n) = a(n-2) + b(n-2) + 1

%C A294862: a(n) = a(n-2) + b(n-2) + 2

%C A294863: a(n) = a(n-2) + b(n-2) + 3

%C A294864: a(n) = a(n-2) + b(n-2) + n

%C A294865: a(n) = a(n-2) + 2*b(n-2)

%C A294866: a(n) = 2*a(n-1) - a(n-2) + b(n-1)

%C A294867: a(n) = 2*a(n-1) - a(n-2) + b(n-1) - 1

%C A294868: a(n) = 2*a(n-1) - a(n-2) + b(n-1) - 2

%C A294869: a(n) = 2*a(n-1) - a(n-2) + b(n-1) + 1

%C A294870: a(n) = 2*a(n-1) - a(n-2) + b(n-1) + 2

%C A294871: a(n) = 2*a(n-1) - a(n-2) + b(n-1) + 3

%C A294872: a(n) = 2*a(n-1) - a(n-2) + b(n-1) + n

%C A022942: a(n) = a(n-2) + b(n-1); offset 1

%C A295998: a(n) = 2*a(n-2) + b(n-2)

%H Clark Kimberling, <a href="https://cs.uwaterloo.ca/journals/JIS/VOL10/Kimberling/kimberling26.html">Complementary equations</a>, J. Int. Seq. 19 (2007), 1-13.

%e a(0) = 1, a(1) = 2, b(0) = 3, so that a(2) = 4

%e (b(n)) = (3,4,5,7,8,10,11,12,14,15,...)

%t mex := First[Complement[Range[1, Max[#1] + 1], #1]] &;

%t a[0] = 1; a[1] = 2; b[0] = 3;

%t a[n_] := a[n] = a[n - 2] + b[n - 2];

%t b[n_] := b[n] = mex[Flatten[Table[Join[{a[n]}, {a[i], b[i]}], {i, 0, n - 1}]]];

%t Table[a[n], {n, 0, 18}] (* A294860 *)

%t Table[b[n], {n, 0, 10}]

%Y Cf. A294861, A294864, A294865.

%K nonn,easy

%O 0,2

%A _Clark Kimberling_, Nov 16 2017

%E Edited by _Clark Kimberling_, Dec 02 2017